PENGARUH PEMBERIAN PUPUK GUANO DAN PUPUK KALSIUM ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH KERITING (Capsicum annuum L.): Tinggi tanaman,Warna daun, jumlah daun, jumlah buah, panjang buah, berat buah - Alamsyah, Marcel Niko; Sigit Saputro, Avisema; Joko Santoso, Sartono (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
The study of the dosage of guano fertilizer and organic calcium from eggshells on the growth and yield of curly red chili plants (Capsicum annum L.) was carried out from July 2024 to November 2024. This research was conducted in Kebak Kalang hamlet, RT 07/RW 05 Kemiri, Kebakramat District, Karanganyar Regency with an altitude of + 105 meters above sea level. The objectives of this study were to: 1. Get the right dosage of guano fertilizer for the growth and yield of curly red chili. 2. Get the right concentration of calcium fertilizer for the growth and yield of curly red chili. 3. Get the interaction of guano and calcium fertilizer administration on the growth and yield of curly red chili. Completely Randomized Design (CRD) 4x4 factorial pattern (CRD) so that 2 factors 16 treatments with 3 replications were obtained. The first treatment factor is guano fertilizer 0 ml/plant, 5 ml/plant, 10 ml/plant, 15 ml/plant and the second factor is organic calcium fertilizer 0 ml/liter, 10 ml/liter, 20 ml/liter, 30 ml/liter. The results of the research data were analyzed using analysis of variance (ANOVA). Then, if there is a significant difference, it is tested at a level of 5% with the Honestly Significant Difference Test (HSD). The results showed that guano fertilizer treatment affected plant height, number of leaves, age of flower emergence, number of fruits per plant, and weight of fruit per plant. Calcium treatment affected leaf color and number of fruits. The interaction of guano fertilizer with calcium affected the number of leaves, number of fruits per plant, weight of fruit per plant, and remaining fruit.